Interaction between diet composition and gut microbiota and its impact on gastrointestinal tract health - Muhammad Shahid Riaz Rajoka; Junling Shi; Hafiza Mahreen Mehwish; Jing Zhu; Qi Li; Dongyan Shao; Qingsheng Huang; Hui Yang (Food Science and Human Wellness)
A substantial amount of emerging research is indicating that the gut microbiota has a significant impact on human health. Alterations of gut microbiota have clear consequences on intestinal homeostasis, physiology, gut microbiome, immune system and host metabolic pathways. Diet composition plays an important role in the control of gut microbial populations and, thus, in the prevention, management and treatment of certain diseases such as cancer, diabetes. A comprehensive analysis of previously reported results revealed that the gut microbiota can be modulated by diet and the composition of gut microbiota can be influenced by various diet components. The symbiotic relationship between different gut microbial communities regulates the immune system and, therefore, any dysbiosis can dysregulate the immune system. Further research is needed to fully understand the mechanisms involved in the interactions between diet composition, gut microbiota and associated diseases.